Taxonomy and Functional Diversity in the Fecal Microbiome of Beef Cattle Reared in Brazilian Traditional and Semi-Intensive Production Systems - Corrêa, Patricia Spoto; Jimenez, Carolina Rodriguez; Mendes, Lucas William; Rymer, Caroline; Ray, Partha; Gerdes, Luciana; da Silva, Vagner Ovani; De Nadai Fernandes, Elisabete Aparecida; Abdalla, Adibe Luiz; Louvandini, Helder (Frontiers in Microbiology, 2021)
The importance of beef production for Brazil’s economy and the growing demand for animal protein across the globe warrant an improvement in the beef production system. While most attention has been on modulation of the rumen microbiome to improve ruminant production, the role of the lower-gut microbiome in host health and nutrition remains relatively unexplored. This work aimed to investigate the taxonomy and functional variations in the fecal microbiome of Brazilian beef cattle reared in two different production systems using a metagenomic approach. Sixty male beef cattle from six farms representing semi-intensive (I, n = 2) and traditional (T, n = 4) Brazilian beef production systems were enrolled in the study. Shotgun sequencing was used to characterize taxonomic and functional composition and diversity of the microbiome in fecal samples collected from each animal. Fecal samples were analyzed for copper (Cu), lead (Pb), nitrogen (N), phosphorous (P), selenium (Se) and zinc (Zn) and stable isotopes of carbon (13C) and nitrogen (15N). The fecal microbiome was influenced by the beef production systems with greater functional and lower taxonomic diversity in beef cattle feces from I systems compared to T systems. The concentration of N, P, and Zn was higher in beef cattle feces from I systems compared to T systems and was associated with taxonomic and functional profile of fecal microbiome in I system, suggesting the role of fecal nutrients in shaping system-specific microbiome. Semi-intensive management practices led to a more complex but less connected fecal microbiome in beef cattle. The microbial community in beef cattle feces from I systems was characterized by greater abundance of beneficial bacteria (phylum Firmicutes and butyrate-producing bacteria family Lachnospiraceae and genera Anaerostipes, Blautia, Butyrivibrio, Eubacterium, Roseburia, and Ruminococcus). In addition, the fecal abundance of microbial genes related to immune system, nutrient metabolism and energy production was greater in beef cattle raised under I systems compared to T systems. Findings of the current study suggest that semi-intensive management practices could facilitate the development of a healthier and more efficient fecal microbiome in beef cattle by driving an increase in the abundance of beneficial bacteria and functional genes.